2018
DOI: 10.1016/j.cmet.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Control of DRP1 Activity Regulates Mitochondrial Dynamics and Bioenergetics

Abstract: Mitochondrial fission-fusion dynamics and mitochondrial bioenergetics, including oxidative phosphorylation and generation of ATP, are strongly clock controlled. Here we show that these circadian oscillations depend on circadian modification of dynamin-related protein 1 (DRP1), a key mediator of mitochondrial fission. We used a combination of in vitro and in vivo models, including human skin fibroblasts and DRP1-deficient or clock-deficient mice, to show that these dynamics are clock controlled via circadian re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
193
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(210 citation statements)
references
References 72 publications
5
193
0
3
Order By: Relevance
“…The two major proteins involved in mammalian mitochondrial fission are Fis1 and Drp1 . Fis1 is an adaptor protein located in the outer mitochondrial membrane, whereas Drp1 is localized in the cytosol, from where it shuttles back and forth to the outer mitochondrial membrane during fission events . Notch was reported to up‐regulate MFN2 expression through the cascade‐up effect of NICD/Akt/Mfn and promote mitochondrial fission .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two major proteins involved in mammalian mitochondrial fission are Fis1 and Drp1 . Fis1 is an adaptor protein located in the outer mitochondrial membrane, whereas Drp1 is localized in the cytosol, from where it shuttles back and forth to the outer mitochondrial membrane during fission events . Notch was reported to up‐regulate MFN2 expression through the cascade‐up effect of NICD/Akt/Mfn and promote mitochondrial fission .…”
Section: Discussionmentioning
confidence: 99%
“…31 Fis1 is an adaptor protein located in the outer mitochondrial membrane, whereas Drp1 is localized in the cytosol, from where it shuttles back and forth to the outer mitochondrial membrane during fission events. 32,33 Notch was reported to up-regulate MFN2 expression through the cascade-up effect of NICD/Akt/Mfn and promote mitochondrial fission. 26,27 On the other hand, it down-regulates Drp1 expression and inhibits F I G U R E 5 Notch1 improves the mitochondrial membrane potential in myocardiocytes exposed to IRI.…”
Section: Discussionsmentioning
confidence: 99%
“…A recent paper showed that Drp1-dependent mitochondrial dynamic was coupled with oxidative respiration: tubular mitochondria was accompanied with increased oxidative respiration, while fragmented mitochondria achieved the opposite [37]. The oxidative phosphorylation activity was supposed to be required in the RLR innate immune signaling, as SeV-induced IFN production was impaired in cells with oxidative phosphorylation defect, but was restored when the oxidative phosphorylation was recovered [38].…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial network is a highly specialized working unit capable of undergoing dynamic adaptation in order to meet metabolic needs and to allow internal and external signaling . Thereby, constant fission and fusion of the inner (IMM) and outer mitochondrial membrane (OMM) play a crucial role in maintaining mitochondrial integrity.…”
Section: Mitochondria As Highly Specialized Working Unitsmentioning
confidence: 99%
“…Mitochondria have undergone a drastic transition from free‐living bacteria to fundamental compartments within eukaryotic cells . Therefore, the mitochondria's broad field of contributions, ranging from production of ATP by oxidative phosphorylation (OXPHOS), buffering of Ca 2+ , and contribution to various cellular signaling pathways, was supplemented with highly dynamic structural and functional adaptations . Stretching throughout the cell as a highly dynamic network along the cytoskeleton, mitochondria are constantly undergoing fusion and fission to meet the requirements of cellular subdomains under various conditions , as discussed in our ‘Mitochondria as highly specialized working unit’ section.…”
Section: Introductionmentioning
confidence: 99%